The Effect of Leadership and Work Discipline on Employee Performance: Study at PT. Agro Afiat Nusantara Company in Barito Kuala - Rina Aprilia; Rina Rina; Fanlia Adiprimadana Sanjaya (International Forum of Researchers and Lecturers, 2025)
This Study aims to examine the influence of leadership and work discipline on employee performance at PT. Agro Afiat Nusantara in Barito Kuala, a non-subsidized fertilizer distribution company operating in South Kalimantan. The research focuses on two main variables: leadership and work discipline, both of which are theoretically considered essential in improving employee performance. A quantitative approach was employed, with data collected through questionnaires distributed to all 30 employees using a saturated sampling method. The data were analyzed using multiple linear regression with the assistance of SPSS (Statistical Package for the Social Sciences) version 27. The analysis revealed that (1) leadership, when tested partially, does not have a significant effect on employee performance; (2) in contrast, work discipline has a positive and significant effect; and (3) simultaneously, both variables significantly contribute to enhancing performance. These findings highlight the crucial role of consistent and structured work discipline particularly in terms of punctuality, responsibility, and adherence to rules as a key factor in supporting employee performance. Practically, the study suggests a reassessment of the leadership style applied within the company and emphasizes the need to strengthen a culture of discipline as part of a sustainable human resource management strategy.